How does transitioning into retirement impact the individual emotional system? Evidence from the Swiss context. (June 2017) - Ryser, Valérie-Anne; Wernli, Boris
Abstract: This article aims to document, from a life course perspective, the impact and timing of the transition to retirement on individuals' emotions—i.e., positive and negative affects—while taking into account their working conditions prior to retirement, and their social participation. Based on the Swiss Household Panel (SHP) dataset, a representative sample of individuals living in Switzerland, results demonstrate that working conditions play a key role in shaping individuals' affective well-being after retirement. Positive work identification is detrimental to affective dimensions after retirement; conversely precarious working conditions before retirement increase positive affects after retirement. Nevertheless, to a lesser extent, the timing of retirement and the capacity of individuals to endorse different roles through social participation also tend to affect the level of affective well-being. Early retirement decreases negative affects, whereas satisfaction with leisure activities upon retirement increases positive affects for men. Finally, these results highlight the heterogeneity in the transition to retirement and the necessity of considering the wide variety of preretirement professional trajectories in the Swiss context.